Perspectives on public space in Rome, from antiquity to the present day - Smith, Gregory; Gadeyne, Jan (Ashgate, 2013)
Divided into five chronological sections (Antiquity, Middle Ages, Renaissance, Baroque, Modern and Contemporary) this volume provides readers interested in urban history with a collection of essays on the evolution of public space in that paradigmatic western city which is Rome. Scholars specialized in different historical periods contributed chapters, in order to find common themes which weave their way through one of the most complex urban histories of western civilization. Through this long-term chronological approach the volume offers a truly unique insight into the urban development